2012
DOI: 10.3748/wjg.v18.i36.5096
|View full text |Cite
|
Sign up to set email alerts
|

Influence ofHelicobacter pyloriinfection on ghrelin levels in children

Abstract: H. pylori eradication increases the plasma and tissue ghrelin levels in children with H. pylori-associated functional dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Similar results were also obtained by Yang et al [101] , who found lower serum ghrelin levels, reduced body weight and height and lower BMI and body weight gain in H. pylori-infected children, with restored ghrelin levels and increased growth observed one year after H. pylori eradication. Increased plasma and gastric mucosal ghrelin levels after H. pylori eradication were also shown by Deng et al [103] in 50 children with H. pylori-associated functional dyspepsia. However, a study reported by Choe et al [109] failed to show a relationship between H. pylori infection and stomach mucosal ghrelin levels, with no effect of eradication therapy.…”
Section: Weight Controlmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar results were also obtained by Yang et al [101] , who found lower serum ghrelin levels, reduced body weight and height and lower BMI and body weight gain in H. pylori-infected children, with restored ghrelin levels and increased growth observed one year after H. pylori eradication. Increased plasma and gastric mucosal ghrelin levels after H. pylori eradication were also shown by Deng et al [103] in 50 children with H. pylori-associated functional dyspepsia. However, a study reported by Choe et al [109] failed to show a relationship between H. pylori infection and stomach mucosal ghrelin levels, with no effect of eradication therapy.…”
Section: Weight Controlmentioning
confidence: 70%
“…Moreover, H. pylori eradication has also been shown to normalize some of these alterations [55,95,[100][101][102][103] .…”
Section: Role Of the Brain-gut Axis In Chronic H Pylori Infectionmentioning
confidence: 96%
“…With similar action as motilin, it has been proposed that the increase in ghrelin level can affect LES pressure and decrease GERD (27). Ghrelin was found to be decreased in both the plasma and gastric cell in H. pylori infection and to be increased after eradication (5,(28)(29)(30). It has been reported that the decrease of ghrelin abolishes the control on LES and increases GERD development (27).…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al. evaluated plasma and gastric ghrelin and body mass index (BMI) before and after H. pylori eradication in 50 children. The authors found that plasma and tissue ghrelin levels significantly increased after successful eradication, although the BMI in the two groups did not differ significantly.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The gastrointestinal hormone ghrelin regulates food intake in humans and a decreased appetite in H. pylori-infected children has been related to lowplasma ghrelin levels, which returned to normal after H. pylori eradication. Deng et al [33] evaluated plasma and gastric ghrelin and body mass index (BMI) before and after H. pylori eradication in 50 children. The authors found that plasma and tissue ghrelin levels significantly increased after successful eradication, although the BMI in the two groups did not differ significantly.…”
Section: Growth Retardationmentioning
confidence: 99%